Papillary renal neoplasm with reverse polarity with a favorable prognosis: Two cases report and literature review - Yuzhi, Zuo; Zhen, Liang; Yu, Xiao; Boju, Pan; Weigang, Yan; Xingcheng, Wu (Frontiers in Oncology, 2022)
Background Papillary Renal Neoplasm (PRN) with polarity inversion is a less common subtype of kidney cancer with an apparently recognizable morphology, distinct immunohistochemical profiles, and frequent KRAS mutations. It has been estimated to account 4% of previously diagnosed PRN. Case presentation This is a retrospective case report of two patients diagnosed with PRNRP. Two males were found to have kidney mass accidentally through imaging examination in clinic. Both of the patients had no obvious discomfort and abnormal test indicators. Subsequently, they underwent partial nephrectomy in our center by the same surgeon and followed up closely with an impressive clinical outcome. The pathology reports indicated that their pathological features were consistent with PRNRP. The HE staining showed a monolayer of papillary or tubular structures, with small nuclei away from the cytoplasmic top of the basement membrane. The immunohistochemical results were GATA3 (+), vimentin (-). Conclusion Our case reports and literature review suggested that PRNRP should be separated from traditional PRN and partial nephrectomy is a robust modality for PRNRP. The morphological, immunohistochemical, and genetic information of the cases we presented would provide important material for PRNRP to become a distinct category with benign clinical outcome.